(untitled) (Medico Legal Update, 2021)
Objectives: To assess the associated factors and complication for women with poly cystic ovarian syndrome. Methodology: A descriptive study conducted on purposive sample of (65) women whom attended Hospitals in Baghdad city suffering polycystic ovarian syndrome for the period of (20th October 2019 through 25th February 2020). Descriptive & Inferential statistical analyses were used to analyze the data. Results: The highest percentages (50%) in age group were (19-22) years, primary schools graduates, housewife, from “urban area”, with irregular cycle. Take high grains, fat, sugar in their food And suffered from obesity, hirsutism, acne,amenorrhea, infertility among short term complication. Conclusions: The study concluded that there is significant relationship between occupation, body mass index, food consumption, dietary habits, environmental factors, with short term complication of PCOS. Recommendations: Need to developed training program to upgrade their knowledge and skills about healthy food and life style to reduction the complication of PCOS.